Ex vivo propofol permeation across nasal mucosa: A proof-of-concept study for outpatient light sedation via nasal route - Michele Domenico Spampinato; Anna Costanzini; Roberto De Giorgio; Angelina Passaro; Nicola Realdon; Fabrizio Bortolotti; Sabrina Banella; Gaia Colombo (International Association of Physical Chemists (IAPC), 2024)
Background and Purpose: Aiming to achieve light sedation via intranasal administration, this study showed that propofol (PPF) did not permeate across the rabbit nasal mucosa ex vivo from its marketed emulsion for injection. Experimental approach: Dilution of the emulsion with methyl-b-cyclodextrin in saline solution increased propofol solubility in water and diffusion across the nasal epithelium. Key results and conclusion: Despite these positive effects of the cyclodextrin, the amount of PPF permeated was minimal in 3 h, exceeding the formulation residence time in the nose. These results highlight the key role of formulation and the need for innovation in solubility and transmucosal transport enhancement techniques to optimize drug delivery and therapeutic efficacy.